2014
DOI: 10.4103/0974-7761.143181
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on attitude toward student-to-student local anesthesia administration

Abstract: Introduction:In the undergraduate dental curriculum, student-to-student administration of first local anesthetic injection remains to be a traditional method in most of the dental institutions. This exercise is often foreseen by heterogeneous emotional responses both in student operator and respondent. Aim: This study evaluated the variations in attitude toward student-to-student LA administration and the associated anxiety levels among the genders. Materials and Methods: 40 female and 24 male preclinical dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…According to the Cugati et al and Meechan studies, women were more anxious about receiving a LA injection than the male participants. These data do not coincide with our study in which no differences between male and female were found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Cugati et al and Meechan studies, women were more anxious about receiving a LA injection than the male participants. These data do not coincide with our study in which no differences between male and female were found.…”
Section: Discussionmentioning
confidence: 99%
“…Though anaesthesia recipients reported the injection of anaesthesia to be painless, the insertion of the needle was more painful for the men. For Cugati et al and Chandrasekaran et al, mixed responses about this topic were obtained. This variability of data depends on many factors, like the relationship between surgeons and recipients, the contact bone during IANB or the rate at which the anaesthesia flowed amongst others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation